Proceedings of the International Conferences on Educational, Social Sciences and Technology - ICESST 2018 2018
DOI: 10.29210/201816
|View full text |Cite
|
Sign up to set email alerts
|

The social meaning of money in social interaction of boarding students

Abstract: The purpose of this research are to reveal social symbols of money, identify the symbolic meaning of money, and explain the social impact of money among boarding students, as well as disclosed by Weber (1978) seeing money is the most perfect means for economic and social transactions. Various studies relating to the meaning of money that has been done previously did not elaborate in depth about it. This researh used mixed method by using interview technique conducted with 79 college boarding house student, boa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
7
0
5
Order By: Relevance
“…Di Minuman keras atau sering disebut miras adalah minuman yang mengandung alkohol dan minuman keras juga memiliki kandungan yang dapat merusak anggota tubuh manusia contohnya minuman keras dapat menyebabkan liver membengkak, merusak otak, kecanduan , bahkan kematian selain memiliki dampak yang buruk bagi kesehatan, pengkomsumsi minuman keras juga mendapat respon negatif oleh masyarakat (Mesra, Erianjoni, & Eriyanti, 2018).…”
Section: Pendahuluanunclassified
“…Di Minuman keras atau sering disebut miras adalah minuman yang mengandung alkohol dan minuman keras juga memiliki kandungan yang dapat merusak anggota tubuh manusia contohnya minuman keras dapat menyebabkan liver membengkak, merusak otak, kecanduan , bahkan kematian selain memiliki dampak yang buruk bagi kesehatan, pengkomsumsi minuman keras juga mendapat respon negatif oleh masyarakat (Mesra, Erianjoni, & Eriyanti, 2018).…”
Section: Pendahuluanunclassified
“…This is shown by the obtained Index at 28.82% (Disagree) to leave the location adjacent to the liquefaction-affected lands. The cultural power is very decisive in social cohesion (socio-cohesion) which applies in a particular community [25,26].…”
Section: A Perceptionmentioning
confidence: 99%
“…Dalam ulasan Romi Mesra yang berjudul The social meaning of money in social interaction of boarding students dimana, ulasannya menjelaskan bagaimana tindakan sosial yang dikaitkannya dengan uang "From the findings of this research, researchers found six symbolic meanings of money, are: There is money there is friend, no problems that can not be solved by money, money is an instrument; (money is the instrument of entry into the community, money is the instrument to enjoy entertainment, and money is the instrument of mobility), money is god, money is the goal, money is "life". (Mesra et al, 2018).…”
Section: Pendahuluanmentioning
confidence: 99%